Evaluation of total white blood cell count as a marker for proviral load of bovine leukemia virus in dairy cattle from herds with a high seroprevalence of antibodies against bovine leukemia virus - Alvarez, Irene; Gutierrez, Gerónimo; Gammella, Mariela; Martínez, Cecilia; Politzki, Romina Paula; González, Cintia Beatríz; Caviglia, Luciana; Carignano, Hugo; Fondevila, Norberto Antonio; Poli, Mario Andres; Trono, Karina Gabriela (2018)
Objective—To determine the reference interval for WBC counts in Holstein dairy cows from herds with high seroprevalence for anti–bovine leukemia virus (BLV) antibodies, analyze the correlation of total WBC counts and blood proviral load (bPVL) in BLV-infected animals, and determine whether total WBC count can be used a hematologic marker for in vivo infection.